2018
DOI: 10.1186/s12929-018-0428-2
|View full text |Cite
|
Sign up to set email alerts
|

Neurochemical changes in basal ganglia affect time perception in parkinsonians

Abstract: BackgroundParkinson’s disease is described as resulting from dopaminergic cells progressive degeneration, specifically in the substantia nigra pars compacta that influence the voluntary movements control, decision making and time perception.AimThis review had a goal to update the relation between time perception and Parkinson’s Disease.MethodologyWe used the PRISMA methodology for this investigation built guided for subjects dopaminergic dysfunction in the time judgment, pharmacological models with levodopa an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 145 publications
(174 reference statements)
0
6
0
Order By: Relevance
“…Clinically, patients with Parkinson’s disease (PD), a basal ganglia disorder involving dopamine deficiency, have provided insights into their influence on temporal processing ( Koch et al, 2009 ; Jones and Jahanshahi, 2011 , 2014a , 2015 ; Magalhães et al, 2018 ). Since PD patients in general present with bradykinesia, that is, slowness of movement, it was speculated that slowness may also involve the temporal processing of the mind.…”
Section: Introductionmentioning
confidence: 99%
“…Clinically, patients with Parkinson’s disease (PD), a basal ganglia disorder involving dopamine deficiency, have provided insights into their influence on temporal processing ( Koch et al, 2009 ; Jones and Jahanshahi, 2011 , 2014a , 2015 ; Magalhães et al, 2018 ). Since PD patients in general present with bradykinesia, that is, slowness of movement, it was speculated that slowness may also involve the temporal processing of the mind.…”
Section: Introductionmentioning
confidence: 99%
“…Also, Pastor et al (1992) compared PD patients with and without medication, observed a significant improvement in the PD patients’ performance under the effect of medication in a verbal estimation task. Thus, considering that the dopamine, as a modulator, tends to accelerate the time perception (Magalhães et al, 2018), reducing the overestimation, the L -dopa, in the present study, would have contributed to the shorter overestimation demonstrated by PD patients when compared with the non-PD participants, without, however, entirely restoring all cognitive performance, such as memory and attention, and motor performance. It should be borne in mind that the artwork manipulation produced temporal overestimation for both PD and non-PD patients, and the effect of the L -dopa was to affect the temporal processing of PD patients reducing the overestimation.…”
Section: Discussionmentioning
confidence: 66%
“…We searched PubMed, Web of Science, and Google Scholar to identify articles published from inception to November 2021, using the keywords “Parkinson’s disease” and “time perception” or “time processing” or “temporal perception,” with English language restrictions. A previous study ( Magalhães et al, 2018 ), consisting of far smaller participant cohorts, have concentrated on in-person visual perception tasks alone. Another study found movement synchronization to visual but not auditory stimuli was impaired by PD ( Wu et al, 2020 ), suggesting a visuomotor timing deficiency in patients.…”
Section: Introductionmentioning
confidence: 99%